Heterostructure from heteromixture: unusual OER activity of FeP and CoP nanostructures on physical mixing - Bhutani, Divya; Maity, Sisir; Chaturvedi, Shashank; Chalapathi, Divya; Waghmare, V. Umesh; Narayana, Chandrabhas; Prabhakaran, Vinod C.; Muthusamy, Eswaramoorthy (Journal of Materials Chemistry A, 2022)
Heterointerfaces generated by inter-domain interactions on a nanoscale play a critical role in altering the activity of an electrocatalyst towards an electrochemical process. Heterointerfaces affect the surface characteristics, electronic structure, and physicochemical properties of a nanomaterial. Herein, we report an FeP-CoP heterostructure prepared by simple physical mixing of FeP and CoP nanostructures showing a remarkable performance towards water oxidation in comparison to their individual monometallic phosphides. FeP mixed with 20 wt% CoP shows a low overpotential (eta(10)) of 220 mV as compared to FeP (eta(10), 325 mV). Furthermore, a high current density of 1.37 A cm(-2) and mass activity of 18 987 A g(M)(-1) were also achieved at 500 mV overpotential in 1.0 M KOH. The physical mixture shows immense stability for 200 h to achieve a high current density of 200 mA cm(-2). Meanwhile the potentiostatic performance of FeP at 200 mA cm(-2) decreases to an extent of 50% in 40 h. A full cell arrangement employing this catalyst as the anode material requires 1.56 V to attain a current density of 10 mA cm(-2). Various characterization techniques, control experiments and theoretical studies indicate that the formation of heterointerfaces between the nano-domains of FeP and CoP results in charge transfer between Fe and Co metal sites. In addition, an oxygenated surface at the metal phosphide interface favours the sorption kinetics of intermediates involved in the reaction leading to low energy barriers in the potential determining and other steps, thus showing improved performance towards water oxidation.